2019
DOI: 10.1177/0269881118821100
|View full text |Cite
|
Sign up to set email alerts
|

3-Furan-2-yl-N-p-tolyl-acrylamide, a highly selective positive allosteric modulator of α7 nicotinic receptors, produces anxiolytic-like activity in mice

Abstract: Background: Several lines of investigations support the idea that nicotinic acetylcholine receptors modulate neuronal pathways involved in anxiety and depression. Aims: The purpose of this study was to determine whether 3-furan-2-yl-N-p-tolyl-acrylamide, a highly selective positive allosteric modulator of α7 nicotinic acetylcholine receptors, influences anxiety-like behaviour in mice, and to determine the modulatory activity of 3-furan-2-yl-N-p-tolyl-acrylamide on mice pretreated with either nicotine or sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…These results confirm the anxiolytic effects of nicotine, which have been previously reported using the same paradigm [4], and emphasise the usefulness of the novel tank diving test as a good model to assess anxiolytic effects. Furthermore, these apparently controversial results, i.e., the anxiolytic effects after nAChR activation or blockade, are in agreement with previous reports showing that both nAChR agonists and antagonists exhibit anxiolytic-like effects in rodents [41][42][43]. Beyond these considerations, our results demonstrate that UFR2709, a novel nAChR antagonist, acts as an anxiolytic drug in this model.…”
Section: Discussionsupporting
confidence: 90%
“…These results confirm the anxiolytic effects of nicotine, which have been previously reported using the same paradigm [4], and emphasise the usefulness of the novel tank diving test as a good model to assess anxiolytic effects. Furthermore, these apparently controversial results, i.e., the anxiolytic effects after nAChR activation or blockade, are in agreement with previous reports showing that both nAChR agonists and antagonists exhibit anxiolytic-like effects in rodents [41][42][43]. Beyond these considerations, our results demonstrate that UFR2709, a novel nAChR antagonist, acts as an anxiolytic drug in this model.…”
Section: Discussionsupporting
confidence: 90%
“…This is a consequence of the higher polarity of the secondary amine of PAM-2, which has a H-bond donor, whereas DM489 is a tertiary amine with no H-bond donor (see Figure ). Previous in vivo animal studies showed that intraperitoneal (ip) injections of PAM-2 induced several behavioral effects in mice, thus suggesting an active brain permeability of PAM-2.…”
Section: Resultsmentioning
confidence: 99%
“…Based on their macroscopic mechanism of action, α7‐PAMs are classified as type I (e.g., NS‐1738) and type II modulators (e.g., PNU‐120596 and PAM‐2) that differ in how they modulate the rate of desensitization and reactivate desensitized receptors (Andersen et al, 2016; Arias et al, 2011; Bertrand et al, 2008; Collins et al, 2011; Papke et al, 2018). Preclinical studies have demonstrated that, besides promnesic and procognitive properties likely mediated by potentiation of the α7 nACh receptor, some α7‐PAMs elicit behavioural effects, such as antinociception and anxiolysis, that may be associated with positive modulation of the GABA A receptor (Alzarea & Rahman, 2019; Arias et al, 2020; Potasiewicz et al, 2017, 2015; Quadri et al, 2018; Targowska‐Duda, Budzynska, et al, 2019). However, to the best of our knowledge, there are no published reports on the activity of α7‐PAMs at GABA A receptors.…”
Section: Introductionmentioning
confidence: 99%